Spanish subjects can be subjects: Acquisitional and empirical evidence - Villa-García, Julio (IBERIA: An International Journal of Theoretical Linguistics, 2014)
The paper provides novel converging acquisitional and empirical evidence from Spanish in support of the hypothesis that preverbal subjects in Spanish can, but need not, be left-dislocated constituents in the CP layer; they can occupy the canonical subject position, Spec,TP, contrary to what is often assumed in the literature. On the basis of acquisitional and statistical evidence gathered from a longitudinal study of five children, the paper argues against Grinstead’s (1998 et seq.) claim that overt subjects emerge in development concurrently with less controversially CP-related phenomena such as wh-questions and dislocations. Moreover, based on the different distributional behavior of genuine subjects and dislocations/foci in the context of desiderative/exhortative sentences introduced by que ‘that,’ the paper argues that Spec,TP/AgrSP is indeed available in Spanish and can only host bona fide subjects to the exclusion of non-subject XPs.